STUDI META ANALISIS MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SD - Sri Wahyuni Siregar; Wildansyah Lubis (JS (JURNAL SEKOLAH), 2023)
Abstract: Study of Meta-Analysis of Role Playing Learning Models on Student Learning Outcomes in Social Studies Learning in Elementary Schools. This research intends to identify the influence of the role playing learning model on the learning outcomes of students in elementary schools. The research method tried is a quantitative analysis of the results of objective research announcements in national e-journals. The results of studies that practice teaching and learning activities using the role playing model are analyzed using the meta-analysis method. Based on the findings of the analysis of research results that have been tried, it can share the following conclusions: the magnitude of the effect of the role playing model on learning outcomes is in the moderate effect category with an average effect size of 0.59, the magnitude of the effect of the role playing model on learning outcomes is in the high effect category with the average effect size is 0.88, the magnitude of the effect of the role playing model on learning outcomes is very high with an average effect size of 1.31 while the magnitude of the effect of the role playing model on learning outcomes is in the high effect category with the average effect sizes 2.39. The research findings reveal that overall the studies carried out have an effect and are effective on social science learning outcomes of students with an effect size of 1.49 which is included in the category of very high effects. The conclusion of this study is to show that learning using the role playing model provides a more effective influence. Keyword: Meta analysis, role playing, effect size, learning outcomes, social scienceAbstrak: Studi Meta-Analisis Model Pembelajaran Role Playing Terhadap Hasil Belajar Siswa dalam Pembelajaran IPS di SD. Riset ini bermaksud buat mengenali besar pengaruh model pembelajaran role playing kepada hasil belajar peserta didik di sekolah dasar. Metode penelitian yang digunakan adalah analisis kuantitatif. Terhadap analisis hasil hasil publikasi penelitian ilmiah pada e-jurnal nasional. Pengaruh penelitian-penelitian yang menerapkan pembelajaran model role playing dianalisis dengan teknik meta analisis. Bersumber pada penemuan analisa hasil riset yang sudah dicoba bisa memberikan kesimpulan selaku berikut: besaran pengaruh model role playing terhadap hasil belajar dengan kategori efek sedang dengan rata-rata effect size 0,59, besaran pengaruh model role playing terhadap hasil belajar dengan kategori efek tinggi dengan rata-rata effect size 0,88, besaran pengaruh model role playing terhadap hasil belajar dengan kategori efek sangat tinggi dengan rata-rata effect size 1,31 sedangkan besaran pengaruh model role playing terhadap hasil belajar dengan kategori pengaruh yang tinggi dengan rata-rata effect size 2,39. Temuan penelitian mengungkapkan bahwa secara keseluruhan penelitian-penelitian yang dilakukan berpengaruh dan efektif terhadap hasil belajar ilmu pengetahuan sosial peserta didik dengan effect size 1,49 yang dimana termasuk dalam kategori efek yang sangat tinggi. Simpulan penelitian ini adalah menunjukkan bahwa pembelajaran menggunakan model role playing memberikan pengaruh yang lebih efektif.Kata Kunci: Meta analisis, role playing, effect size, hasil belajar, ilmu pengetahuan alam